The Source and Explosion of African Pentecostalism and Globalization - Oyeku, Samson Kolawole (KWASU Journal of Religious Studies, 2018)
The Holy Spirit led the Early Church which was a community where freedom of expression and spontaneity that characterized its worship may not have been very different from that of many Pentecostal churches today. The beginning, spread and explosion of the Pentecostal movement is extraordinarily great globally, more especially among many African Indigenous Churches with a Pentecostal zeal. Presently, Christians can be found in almost every country in the world. Although Christianity has been gradually expanding since its earliest days, its globalizing presence is not old in human history. The effects of Pentecostal movements can be categorically felt across the globe today, and there is hardly a Christian denomination or sect which has not in one way or the other been influenced by this movement. One of the obvious questions that arise is that, what accounts for the beginning, explosive and extraordinary growth of African Pentecostalism and Globalization? This paper traces the source or the beginning of the Pentecostal movement and the rapid explosion involved in its spread across the globe in general and Africa in particular, between the twentieth and twenty-first centuries of the present era. The positive and negative impacts of the movement's on African Christianity are also examined. Since the topic has to do with church history, the study uses the historical perspective and qualitative method which is Africanist in approach to church historiography, which is marked by total and objective commitment to Africa.